Strategi Optimalisasi Google Profile Business dalam Meningkatkan Visibilitas Online Glowmax - Fikri Akmal Ash Shiddieqy; Cecep Safa'atul Barkah (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
In the context of Indonesia's rapidly growing beauty and personal care industry, this research focuses on optimizing the Google Business Profile strategy for Glowmax, a beauty clinic in East Bekasi. Despite significant market potential, Glowmax faces internal challenges such as limited human resources and low digital literacy, which hinder online visibility and the ability to attract new clients. This study aims to bridge this gap by applying the SOSTAC (Situation Analysis, Objectives, Strategy, Tactics, Action, Control) strategic planning model to optimize Glowmax's digital presence. A qualitative descriptive research method was employed to analyze the implemented strategies and their results. The strategies included comprehensive profile completion, proactive review management, and regular content updates. The results show a significant increase in Google Maps profile views, from a target of 46 to 395 views within one month (June 1-30, 2025). Additionally, 177 customer interactions were recorded, indicating increased attention and engagement from potential customers. These achievements demonstrate that optimizing the Google Business Profile not only enhances visibility but also positively impacts business reputation and attractiveness, ultimately contributing to increased conversions such as new appointments and sales. Therefore, systematic management of the Google Business Profile is a crucial strategic step for MSMEs to compete in the digital era.